The Influence of the Tarl Model to Improve Students' Reading Literacy Skills in the Indonesian Language Subject for Grade III of SDN 24, Bima City - Nufus, Hayatun; Khusaini , Fakhri; Kurniawan , Edy (Journal of Educational Sciences, 2025)
Reading literacy is a basic skill that plays an important role in the learning success of elementary school students. However, observation results show that third-grade students of SDN 24 Kota Bima still experience difficulties in understanding reading texts, finding main ideas, and reorganizing information. This study aims to examine the effect of the Teaching at the Right Level (TaRL) model on students' reading literacy skills. The method used was a quasi-experimental with a one-group pretest-posttest design and involved 18 students as a sample. The instrument was a reading literacy questionnaire consisting of 14 Likert-scale statements. The results showed that the average pretest score of students was 62.78, categorized as sufficient, while the average posttest score increased to 83.33, categorized as good. The Shapiro-Wilk normality test showed that the pretest data were normally distributed (p = 0.073 > 0.05), while the posttest data were not normally distributed (p = 0.008 < 0.05). However, the paired t-test results showed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest results. Thus, the implementation of the TaRL model has a positive effect on improving students' reading literacy skills and can be used as an alternative innovative learning model in elementary schools.